Tapping into student’s passion, curiosity, engagement and dreams: engineering educator’s task - Ahmad, Zuraida; Halim, Zahurin; Mohamad, Souad A.; Salleh, Md. Noor; Ismail, Ahmad Faris (Sci.Int.(Lahore), 2014)
Engineering education faces significant challenges as it seeks to meet the demands on the engineering profession in the twenty-first century. The engineering faculty /Kulliyah will need to continue to learn new approaches to teaching and learning, which in turn will require effective professional development for both new and experienced educators alike. This paper explores approaches to an effective professional development and provides a conceptual framework for responding to the challenge of becoming a professional engineering educator. The practice is introduced as prelude for identifying what individual educators and the institutions can do to generate more effective forms of engineering education. The paper also include a case study that illustrate the possibilities when faculty/kulliyyah and educators join together in addresing calls for challenge.